THE ESSENCE OF GENERAL EDUCATION - Alexander A. Frolov (Russian State Vocational Pedagogical University, 2015)
The aim of the investigation is to disclosure essence, purpose and coherence of the system of general education through its subject content. Methods. The methods involve literature overview, theoretical research and observation. Combined application on the methodological level has provided a systematic approach to identifying the goals of general education and the structuring of its substantive content. Results. The development of students' speculative powers should be the main task of general education whereby they can create individual model representation according to form but meaningfully adequate to the real life. The scheme of model representations development in the process of general education is proposed. Scientific novelty. The pedagogical model of development of educational process is proposed as the instrument of educational and social adaptation for students; the model represents a logical sequence of formation by students an adequate model of reality with increasing complexity. Practical significance. The proposed pedagogical model allows considering the process of general education mastery and development in absolute unity of its subject content, which should lead to the formation and development of competence in the field of adequate modeling of situations of reality.